Application of RFID in Shaheed Rajguru College of Applied Sciences for Women Library, University of Delhi, India: Challenges and Future Prospects - Roy, Projes; Kumar, Shailendra (Qualitative and Quantitative Methods in Libraries, 2017)
The paper studied many aspects of the RFID application, its budgeting, purchase process and application. It also studied advantages and limitation of RFID Technology, Documentation and Financial Implication, Challenges faced in initial stage and remedies. A structured questionnaire was designed to collect the raw data. This study employs the method of quantitative research to gather an in-depth understanding of the nature of usage of RFID system among users of SRCASW (Shaheed Rajguru College of Applied Sciences for Women) library. This study shows many authentic conclusions on data accuracy, speedy circulation, easy book identification, extension of library service, cost effectiveness, security of library materials and other value added services. Orientation program for the RFID enabled is very much important. The NFC technology can be used along with the RFID, as the application radio frequency is same in both the technology , this also incorporated in this study.